Tools of Change for Publishing Conference, New York 2012 : complete video compilation. (O'Reilly Media, 2012)
"The acceleration of change and innovation in the publishing industry today is dizzying, and the pace can be overwhelming. At O'Reilly's TOC New York Conference in February 2012, practitioners and executives from the publishing and tech industries joined together to navigate the ongoing transformation. With this video compilation, you'll get a seat in the front row of every session at this groundbreaking conference."--Resource description page.